Influence of long days on the production of cut chrysanthemum cultivars - Zandonadi,Alessandra S (2018)
ABSTRACT Chrysanthemum is one of the most widely marketed cut flower in the world. For this flower cultivation, long days to induce vegetative growth are required, until the plant reaches the necessary size for commercial flowering. The aim of this study was to evaluate the influence of the number of long days on the production of floral stems of five cut chrysanthemum cultivars. The experiment was evaluated in a randomized block design with split plots, with two factors and three replicates. Considering the number of long days (21, 28, 35, 42 and 49) the plots, and sub-plots the cut chrysanthemum cultivars (Calábria, Dragon, Sheena, Apricot Repin and Rebasco). We noticed significant differences for most of morphological traits for number of long days, and for interaction of cultivar x number of long days. Dragon, Apricot Repin and Calábria were the cultivars which stood out producing greater vigor of stems and better agronomic quality. Sheena and Rebasco cultivars showed the lowest performance among the evaluated cultivars, though. The cut chrysanthemum cultivars showed agronomic performance which allows a reduction in the number of long days of exposure, from 35-45 days usually practiced, to 21-28 days, reducing the time required for commercialization.